Krivičnopravni aspekt govora mržnje kao zloupotreba prava na slobodu izražavanja / The Criminal Aspects of Hate Speech as Abuse of the Right to Freedom of Expression - Ferhatović, Amila; Trlin, Davor (Pregled: časopis za društvena pitanja / Periodical for social issues, 2020)
The authors analyze the right to freedom of expression as one of the fundamental human rights, important for every individual and for every democratic state. However, given that this right is not absolute, the authors seek to determine its boundaries, especially with regard to hate speech. This is a very actual topic in recent years in Bosnia and Herzegovina. This is due, on the one hand, to frequent statements that the public perceives as potential hate speech and, on the other, a small number of criminal proceedings. Following an introductory review of relevant international sources, the authors focus on the conceptual definition of hate speech. The following section analyzes Bosnia and Herzegovina legislative and case law, as well as individual judgments of the European Court of Human Rights. The aim of the paper is to draw attention to current issues of concern and to provide guidance on how to resolve them, based on an analysis of the international and domestic legal framework, and the available case law of the courts of Bosnia and Herzegovina and the European Court of Human Rights.